Clinicopathological characteristics of severe aortic valve regurgitation caused by Behçet's syndrome - Zhang, Menghao; Wang, Xun; Liu, Yeling; Liu, Xinpei; Yu, Xin; Sun, Luxi; Wang, Zhimian; Zhang, Lifan; Liu, Jinjing; Ma, Guotao; Chen, Wei; Wang, Wenze; et al. (Clinical and experimental rheumatology, 2025)
Aortic valve regurgitation (AR) caused by Behçet's syndrome (BS) has high mortality. Preoperative biologics reduced systemic inflammation, but their effect on lesion inflammation remains unclear. Twenty-two BS patients with severe AR who underwent cardiac surgery with retained pathological specimens were included. The pathology of the aortic wall and/or valve was re-analysed based on their preoperative disease activity and treatment strategy. Immunohistochemistry (IHC) assessed the distribution of CD4+, CD8+, CD20+ and CD68+ cells. The mean diagnosis age was 39.6±13.1 years, with a median disease duration of 9 (3-35) years. Seven (31.8%) underwent cardiac surgery during the active phase due to uncontrollable disease progression, while 15 (68.2%) were in remission. Pathologically, severe AR caused by BS is characterised by mixed inflammatory cell infiltration in the aortic wall. Active cases showed significantly more diffuse infiltration of CD4+ (100% vs. 8.3%, p=0.0002) and CD8+ (71.4% vs. 20%, p=0.058) T cells in the aortic adventitia, with more neutrophil infiltration in the aortic valve (60% vs. 7.7%, p=0.044). Notably, less CD68+ macrophage infiltration (57.2% vs. 0%, p=0.045), CD4+ T cell diffusion (57.1% vs. 0%, p=0.045), and vasa vasorum mucoid degeneration (85.7% vs. 20%, p=0.017) were observed in the aortic adventitia of patients receiving preoperative biologics, together with less aortic valve necrosis (71.4% vs. 0%, p=0.023). Overall, our study provides valuable insights into the pathology of severe AR caused by BS as a mixed inflammatory infiltration and provides the first pathological rationale for achieving preoperative remission and early biologics to improve the prognosis.